GAMBARAN TINGKAT PENGETAHUAN TENAGA TEKNIS KEFARMASIAN TENTANG TINDAKAN ASEPTIC DISPENSING DI RSUD DR. MOEWARDI SURAKARTA - Damayanti, Ina; Murtisiwi, Lusia (Jurnal Farmasi (Journal of Pharmacy), 2022)
knowledge about aseptic dispensing at RSUD Dr. Morwardi. This research is a non experimental research with a descriptive survey design. The sampling technique in this research is total sampling. The sample in this study amounted to 50 people. Respondent’s knowledge data was collected using a questionnaire with a total of 10 questions that had been tested for validity with Pearson’s correlation and reliability test with Cronbach’s Alpha which was then analized using SPSS 25. The results showed that knowledge about standard precautions was good, as many as 44 people (88%). Respondents with sufficient knowledge were 4 people (8%), and with poor knowledge were 2 people (4%). The conclusion of this study is that the level of knowledge of pharmaceutical technician about aseptic dispensing at RSUD Dr. Moewardi is good.